2019
DOI: 10.3390/ijms20174167
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Secreted Proteome of Trametes versicolor for Controlling the Cereal Pathogen Fusarium langsethiae

Abstract: Fusarium langsethiae is amongst the most recently discovered pathogens of small grains cereals. F. langsethiae is the main producer, in Europe, of T2 and HT-toxins in small grain cereals, albeit often asymptomatic; this makes its control challenging. The European Union (EU) is pushing hard on the use of biocontrol agents to minimize the use of fungicides and pesticides, which are detrimental to the environment and responsible for serious pollution of the soil and superficial water. In line with EU directives (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In addition, nowadays the EC policy is driving research to investigate more environmentally friendly “green” approaches. This has increased the research on the development of biocontrol strategies as well as the use of natural plant extracts to control and mitigate the presence of mycotoxins in food and feed [ 20 , 21 , 22 , 23 , 24 ]. One of the promising tools for mycotoxin (particularly aflatoxins) control, with lower environmental impact, are the metabolites of higher mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nowadays the EC policy is driving research to investigate more environmentally friendly “green” approaches. This has increased the research on the development of biocontrol strategies as well as the use of natural plant extracts to control and mitigate the presence of mycotoxins in food and feed [ 20 , 21 , 22 , 23 , 24 ]. One of the promising tools for mycotoxin (particularly aflatoxins) control, with lower environmental impact, are the metabolites of higher mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the discovery of the very active part of the polysaccharide would be especially relevant, from an economic point of view, as its synthesis could be more cost effective. Moreover, fungal and plant extracts could represent a promising tool in mycotoxin control, compared to chemicals [ 39 , 40 , 41 , 42 , 43 ], due to their lower toxicity when released into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the mycelia were separated from the culture filtrates by subsequent filtrations through 0.45 μm filters (Sartorius, Goettingen, Germany), to eliminate all the mycelia. Mycelia-purified culture filtrates were concentrated in rota-vapor (Rotavapor ® R-300, Buchi, Essen City, Germany), and up to a concentration of 100 mL as described by Parroni and collaborators [ 42 ]. Concentrated culture filtrates were lyophilized and utilized for subsequent analyses as reported in [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cruz analyzed the effects of soil conditions (soil texture, pH, and soil moisture) on Fusarium graminearum when planting (Jimenez et al, 2020). Parroni et al (2019) reported the use of Trametes versicolor for Controlling the cereal pathogen Fusarium langsethiae. Wei (2019) screened for Acrocalymma from soil around the coal mine and found that Acrocalymma formed a symbiotic relationship with alfalfa and sand Holly and promoted the uptake of nitrogen and phosphorus by plants.…”
Section: Differences In the Endophytic Bacteria Of Different Varieties Of Cajanus Cajanmentioning
confidence: 99%